Humor in Turkish Literature - Stojisavljević, Vojna (Prilozi za orijentalnu filologiju, 2017)
Humor and satire are occupying very important part in all sorts of turkish people's artistic expressions. Turkish poet is painting at vices and mistakes, then forgiving them through serene laughter well-intentioned rebuke; sometimes, that laughter becomes crude and unmerciful, even going to extremes. In such cases, it is very difficult to determine the boundary between humor and satire. With this study we have tried to point at the basic characteristics of that humor, as well as at the artistic forms it was presented in, during the long lasting period of turkish literature. We were guided by widely accepted periodization of turkish literature. Sadly, we do not know much about the characteristics of humor in old anadol literature, the reason being solely oral tradition of that literature. Through seleuk humor (which we have marked as the second phase) we are able to follow the processes of social divide, rise and fall of the seleuk saray, establishment of strong Ottoman saray and blooming of anadol culture. Thus, the humor in the oral tradition of turkish tribes is at first naive, decorated with motives of steppes, nomadic life and surreal events, full of sacred phrases and appeals to God, without the traces of urban culture. lt is to be found in the epic "Dede Korkut kitabi" and in the singings of hero Keloglan. Period between the fall of seleuk and the rise of Ottoman saray is marked by the occurence of tarikats (dervish orders), whose eminent members were also known as the first great humorists. A very special place among them belongs to the great folk sage Nasrettin Hoca. His anecdotcs and jokes (fıkra, hikâ'iye) were, and still, to the prcsent day, are popular amongst the turkish people; writers of the Tanzimat period turned to them in trying to create modern turkish literature. Bektashi dervish order has always been cherishing the humor criticizing different social phenomenons in islamic society. That humor's inexhaustible vitality and actuality is easily confirmed even today, thanks to the group of writers who collected its examples around anadol villages during the forties of this century.